2000
DOI: 10.1097/00002820-200012000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adolescent Cancer Survivors Who Pursue Postsecondary Education

Abstract: This study aimed to identify differences between adolescent cancer survivors who participate in postsecondary education and those who do not, as well as factors that helped these survivors to cope. American College Testing records for 129,824 adolescents were meshed with Iowa's Cancer Registry to identify Iowans who had received a diagnosis of cancer between the ages of 12 and 17 years. The potential subject pool contained 85 persons. A questionnaire was sent to the 28 persons who agreed to participate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…[17][18][19]23,33,34,37,[39][40][41][42][43]48,55,68,72,73,[80][81][82][83][84] Distress caused by fatigue was the most commonly described impact, reported in 11 studies. The MSAS, a scale that allows comparison of the level of distress caused by each symptom, was used in six of these studies.…”
Section: Impact Of Fatiguementioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19]23,33,34,37,[39][40][41][42][43]48,55,68,72,73,[80][81][82][83][84] Distress caused by fatigue was the most commonly described impact, reported in 11 studies. The MSAS, a scale that allows comparison of the level of distress caused by each symptom, was used in six of these studies.…”
Section: Impact Of Fatiguementioning
confidence: 99%
“…17 One study reported that distress was correlated with the frequency and severity of fatigue. 34 The remaining five studies used diverse measures of distress, 40,43,55,82,83 and fatigue was one of the top four most distressing conditions in four of these studies. 40,43,82,83 The second-most frequently described impact of fatigue was that it was a barrier to physical activity or exercise, which was reported in six studies.…”
Section: Impact Of Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…It affects children and adolescents with cancer at all stages of the disease trajectory from diagnosis to survivorship and the end-of-life period [4][5][6][7][8][9][10][11][12][13][14][15]. Fatigue has physical, mental, and emotional components and may be characterized by a lack of energy, decreased physical ability, and feelings of tiredness.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that adolescents worry that information is withheld from them; inadequate information is regarded as the second most important problem after physical symptoms caused by illness 7. In a questionnaire study, Griffith and Hart 8 identified the factors that helped adolescent survivors cope, and one important factor was to take part in decision‐making concerning their care.…”
Section: Introductionmentioning
confidence: 99%